Prevalence of anxiety and depression symptoms and associated factors among women diagnosed with breast cancer: A cross-sectional study at Ocean Road Cancer Institute in Dar es Salaam–Tanzania - Ummy Msenga; Joel S. Ambikile; Salome E. Buluba (PLoS ONE, 2025)
Introduction Anxiety and depression are the prevailing mental illnesses in low and middle-income nations. The shock of receiving breast cancer diagnosis and it’s effects on daily life make it perplexing to adjust to the situation, hence anxiety and or depression symptoms develop. This study aimed to determine the prevalence and factors associated with anxiety and depression symptoms among women diagnosed with breast cancer at Ocean Road Cancer Institute (ORCI) in Dar es Salaam, Tanzania. Methods We conducted an analytical quantitative cross-sectional study between May and June 2023 among 384 women diagnosed with breast cancer using consecutive sampling. We used a pre-tested interviewer-administered questionnaire to collect data and the Statistical Package for Social Sciences (IBM SPSS) version 23 for data analysis. Bivariate and multivariate logistic regression analyses were performed to identify factors associated with anxiety and depression symptoms, and a p-value <0.05 was considered statistically significant. Results We found a relatively high prevalence of anxiety (44.8%) and depression (50.5%). Participants who didn’t know their stage of cancer [adjusted Odds Ratio (aOR): 0.39; 95% Confidence Interval (CI): 0.19, 0.83; p = 0.014]; in early stage of cancer [aOR: 0.36; 95%CI: 0.16, 0.81; p = 0.014]; with low state of hope [aOR: 0.52; 95%CI: 0.31, 0.86; p = 0.012]; and low cognitive reappraisal [aOR: 2.09; 95%CI: 1.33, 3.28; p < 0.001] were significantly associated with anxiety. Those without partners [aOR: 2.56; 95%CI: 1.59, 4.10; p < 0.001]; didn’t know their stage of cancer [aOR: 0.38; 95%CI: 0.17, 0.86; p = 0.020]; receiving radiotherapy treatment [aOR: 3.86; 95% CI: 1.34, 11.08; p = 0.012]; and low cognitive reappraisal [aOR: 2.41; 95%CI: 1.52, 3.83; p < 0.001] were significantly associated with depression. Conclusion Symptoms of depression and anxiety were very common among women diagnosed with breast cancer in this study. We strongly advise for proper care including routine screening from mental health specialists to improve treatment outcomes among this population group.